Why we need water and fiber - Royston, Angela, 1945- (St. Catharines, Ont. ; New York : Crabtree Pub., 2011)
Examines the nutritional benefits of water and fiber and discusses how they help the digestive system function.
Includes bibliographical references (p. 47) and index.
Resource Links
Resource Links, June 2011
6.4
5-8
5-8
Keywords: Fiber in human nutrition -- Juvenile literature; Water in the body -- Juvenile literature; Fiber in human nutrition; Water in the body; Food -- Fiber content; Human body; Water